Pengaruh Regulasi terhadap Validitas Akad Ijarah dalam Pembiayaan Multijasa Syariah: Studi Kasus di Indonesia - Septiayu R Wulandari (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2022)
This study explores the impact of regulations on the validity of Ijarah contracts in Sharia multi-service financing in Indonesia. Strict and clear regulations are necessary to ensure compliance with Sharia principles, transparency in transactions, and protection of customer interests. The research adopts a qualitative approach, analyzing the implementation of regulations and the perceptions of stakeholders in the Islamic finance industry. Findings highlight challenges faced by Islamic banks, including evolving regulatory complexities and the need for adequate resources. Customers tend to feel more confident and secure when transactions are conducted under consistent and structured regulations. Regulators are recognized as playing a crucial role in ensuring stability and growth in the Islamic finance industry through well-implemented regulations. Regulations in Indonesia play a crucial role in governing various aspects of implementing Ijarah contracts in the Islamic finance industry. These regulations encompass the requirements to be met, execution procedures, and oversight mechanisms to ensure compliance with Sharia principles, transaction transparency, and customer protection. Clear and stringent regulations not only enhance the validity of Ijarah contracts but also support stability and growth in the Islamic finance industry. Nevertheless, Islamic banks face challenges such as evolving regulatory complexities, the need for adequate resources, and uniform interpretation of regulations across business units. Customers tend to have greater trust and feel more secure when transactions are conducted under stringent and clear regulations, while regulators view regulations as vital tools for maintaining stability in the Islamic finance industry. Keywords: Regulations, Ijarah contracts, Sharia principles, transparency, customer interests